The Corporate Form of Innovating Entities in Ukraine - Zelisko, A.; Rozghon, O. (Science and Innovation, 2022)
Introduction. High risk associated with innovation requires reducing possible losses during the implementation of innovation as much as possible. The form of a legal entity is a means of achieving this goal. It allows separating the obligations of legal entity from those of its members. Problem Statement. The legislation of Ukraine and foreign states contains numerous forms of legal entities in the sphere of innovation. Therefore, it is necessary to systematize them. Purpose. The purpose of this research is to from a single vector of systemic legal regulation of legal entities in the field of innovation based on the analysis of domestic and foreign doctrine and legislation. Material and Methods. In the process of research, a complex of general scientific and special methods has been used. Materials for the study are the publications of domestic and foreign researchers, the applicable legislation of Ukraine and foreign countries. Results. The comparative analysis of the doctrine and practice of foreign states has shown dispositive approaches of legislation of different states to the differences between the science parks and the technology parks and their ties with R&D or educational institutions in them. However, the systemic legal regulation of such legal entities needs the application of their common concept that will be the basis for unified approaches to this problem. Conclusions. Public interest essentially influences the studied legal entities and defines their exclusive legal capacity; special procedure for their creation; special status of innovating entity; special requirements to the structure of founders; specific features of contributions to the authorized capital; the requirement of the presence of innovation project.